(untitled) (Journal of Universal Science Research, 2025)
This article explores compound words in the Russian language that express emotional states and attitudes. Through the lens of linguistics and cultural semantics, we analyze how these compounds are formed, their syntactic and morphological structures, and their role in expressing culturally specific emotions. The study also highlights the influence of Russian worldview and national character on the language’s emotional vocabulary.